Damping of low-frequency oscillations and improving power system stability via auto-tuned PI stabilizer using Takagi-Sugeno fuzzy logic - Hassan, L.H.; Moghavvemi, M.; Almurib, H.A.F.; Muttaqi, K.M.; Du, H. (Elsevier, 2012)
This paper proposes a Takagi-Sugeno (TS) fuzzy gain-scheduling PI stabilizer to damp the power system low-frequency oscillations and enhance power system stability. The work describes the construction of appropriate fuzzy membership functions and rules for a Power System Stabilizer (PSS) so that its proportional and integral gains can be automatically tuned in real-time to react to changes in the system operating conditions. To find the optimal number and locations of required stabilizers, this paper uses the participation factor method. Simulation results on a practical power system demonstrate that the proposed stabilizer is effective in damping low-frequency oscillations as well as improving system dynamic stability and voltage profile. In addition, the proposed approach provides superior performance when compared to a conventional PI PSS. © 2011 Elsevier Ltd. All rights reserved.